PENGARUH PENGETAHUAN PERPAJAKAN, KUALITAS PELAYANAN PAJAK, SANKSI PAJAK DAN SIKAP WAJIB PAJAK TERHADAP MOTIVASI WAJIB PAJAK ORANG PRIBADI DALAM MEMBAYAR PAJAK DI SEMARANG - Ririn Meylena, 16.05.62.0001; Wahyudi, Djoko (Students Journal of Accounting and Banking, 2018)
This study aims to examine the influence of taxation knowledge, the quality of tax services, tax sanctions and attitudes of taxpayers on the motivation of taxpayers of individuals in paying taxes. The number of samples in this study were 100 respondents. Respondents who become the sample of this study are taxpayers who have a job / free effort on the KPP in the city of Semarang that routinely reported tax obligations. The sampling technique used in this research is to use purposive sampling that is sampling with criteria that is Taxpayers who have job / free effort at KPP in Semarang city that routinely report tax obligation. Methods of data analysis using linear regression. From the research results can be taken some conclusions that knowledge about taxes, service quality, tax sanctions and attitudes of taxpayers have a positive and significant impact on taxpayer motivation.Keywords: tax knowledge, tax service quality, tax sanction, taxpayer attitude and taxpayer motivation